ANTI HCV DAN JUMLAH PENDERITA JANGKITAN (PREVALENSI INFEKSI) VIRUS HEPATITIS C - Isti Setijorini Wulandari; Kismardhani . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
ABSTRACTIn various prevalence Hepatitis C Virus (HCV) infections was found all over the world. There is no accurate data about the spreading of HCV infection in Indonesia. Indonesian Department of Health makes a program to make a database from all provinces in Indonesiaabout prevalence of HCV. This is supported by request from the district Health Department of Daerah Istimewa Yogyakarta (DIY)Province to conduct HCV infection surveillance in 2007. Data of HCV infection from blood transfusion service show approximately 2%.To complete the basic data by knowing the prevalence of HCV in Dr. Sardjito General Hospital Yogyakarta at DIY province. This is an Hospital Yogyakarta at DIY province. This is anHospital Yogyakarta at DIY province. This is an observational descriptive study about HCV infection prevalence in Dr. Sardjito General Hospital Yogyakarta. Data was collected fromSeptember 2007−August 2008 conducted on Microbiology, Immunology & Infection Sub Laboratory of Clinical Pathology Departmentin Dr Sardjito General Hospital Yogyakarta. There was 753 request of anti HCV test from September 2007−August 2008. Initial reactiveresult was found in 131 patients. In the first quarter in 2007 (January−April 2007) there were 27 initial reactive from 175 samples ofanti HCV test (15.42%). In the second quarter were found 36 initial reactive out of 176 samples of anti HCV test (20.45%) and in thelast trimester in 2007 were found 19 initial reactive out of 134 samples (14.17%). In 2008, first quarter were found 21 positive resultout of 123 samples (17.03%) and in the second quarter (May−August 2008) were found 32 positive result out of 145 samples (22.06%).There are gradually increased percentage rates of initial reactive anti HCV test based on the result from each trimester HCV test based on the result from each trimesterHCV test based on the result from each trimester (15.42−20%, 45−14 %, 17−17%, 03−22.06%)